Cover Feature: A Hydroxylated Tetracationic Viologen based on Dimethylaminoethanol as a Negolyte for Aqueous Flow Batteries (Batteries & Supercaps 1/2023). Issue 1 (15th December 2022) - Caianiello, Carlo; Arenas, Luis F.; Turek, Thomas; Wilhelm, René
Abstract : The Cover Feature illustrates the structure of a new hydroxylated tetracationic viologen based on dimethylaminoethanol in an aqueous solution from different angles. The compound showed an enhanced solubility, high electrochemical reversibility and was used as negolyte in a proof‐of‐concept flow battery. More information can be found in the Research Article by R. Wilhelm and co‐workers .